Curator, curator - Gouwenberg, Maaike; Vanden Eynde, Maarten; Enough Room for Space, Gent; HISK, Gent ([Gent] : HISK, 2010)
Saebjörnsson, Egill ; Tampere, Karolin ; Bruni, Lorenzo ; Wielebska, Kamila ; De Blaaij, Remco ; Yildiz, Adnan ; Maier-Rothe, Jens
Publication on the occasion of the exhibitions 'Curator curator' at the HISK at Ghent, 2008-2010
boek